Deriving Extracellular Vesicle Size From Scatter Intensities Measured by Flow Cytometry. Issue 1 (31st August 2018) - de Rond, Leonie; Coumans, Frank A. W.; Nieuwland, Rienk; van Leeuwen, Ton G.; van der Pol, Edwin
Abstract: Flow cytometry is commonly used to investigate the potential for extracellular vesicles (EVs) to be biomarkers of disease. A typical flow cytometer detects fluorescence and scatter intensities of single EVs in arbitrary units. These arbitrary units complicate data interpretation and data comparison between different flow cytometers. For example, comparison of detected EV concentrations requires knowledge of the detectable EV sizes. Using Mie theory and knowledge of the optical configuration of the flow cytometer, EV size can be derived from the scatter intensity for a given EV refractive index. Here, a protocol is described to derive the size of EVs and other nanoparticles from the scatter intensity. The resulting size distribution allows the comparison of data between flow cytometers, which is a prerequisite for clinical application of EVs as biomarkers and may advance other fields where sizing of nanoparticles is essential. © 2018 by John Wiley & Sons, Inc.